The effects of social media towards internal communication among employees during Covid-19 lockdown / Nur Syahira Md Subre, Ahlam Abdul Aziz and Dzaa Imma Abdul Latif - Md Subre, Nur Syahira; Abdul Aziz, Ahlam; Abdul Latif, Dzaa Imma (Faculty of Information Management, 2023)
This study aims to identify the effects of social media on internal communication among employees during the Covid-19 lockdown. During the Covid-19 outbreak, social media can be used as a platform to assist employees in communicating with each other. This study investigated social media usage among employees during the Covid-19 lockdown. A quantitative approach was undertaken to answer the research questions. The questionnaire was designed in three sections: demographic information, general usage of Facebook among employees during the lockdown and the effects of social media on internal communication among employees during the lockdown. The results showed that the main purpose employees used social media during lockdown was to stay updated with their friends, and the results also showed that the most used social media among employees during the lockdown was Facebook, in fact, most respondents agreed that social media is a good platform to initiate good rapport with colleagues during the lockdown. As a result of this study, it was found that social media played a vital role in helping employees maintain good relationships with each other through social media during the Covid-19 lockdown.